The Influence of Students' Attribute on Earthquake Understanding in Klaten Regency - Dewi, Ratih Puspita; Musiyam, Muhammad; Widiyatmoko, Wahyu; Wibowo, Yunus Aris; Suharjo, Suharjo; Miftakhunisa, Yunita; Khoirunnisa, Hakimah (Universitas Negeri Medan, 2024)
An earthquake is a type of natural disaster that cannot be predicted in terms of time or scale. Klaten Regency is one of the earthquake-prone areas of Indonesia. The occurrence of earthquakes in Klaten Regency has indeed surprised many parties. Implementing disaster mitigation measures is crucial in areas prone to disasters. Disaster mitigation education has been implemented in schools through intracurricular and extracurricular activities. This study aims to analyze (1) the student's understanding of earthquakes at the elementary, middle, and high school levels in Klaten Regency and (2) the impact of student attributes on an understanding of earthquakes. Students' Students comprise age and gender. This is a quantitative study with a correlational research approach. The study was 173 students from junior high school. Techniques for collecting data include questionnaires and documentation. Data analysis techniques employ descriptive statistics; furthermore, the tests used to answer the hypothesis are the Mann-Whitney test, kruskall Wallis, and Spearman rank. The Mann-Whitney test. According to the study results, (1) students' students' of earthquakes was 22% high, 75% moderate, and 3% low, and (2) The test results pointed out that student characteristics had no significant impact on students' student's knowledge.Keywords: Earthquake; Disaster; Students; Understanding of Disaster